Efficacy of a pheromone-impregnated collar in controlling feline problem behaviors, and an assessment of adverse events associated with collar use - Endersby, Sarah; Billy, Charlotte; De Jaeger, Xavier (Frontiers in Veterinary Science, 2024)
The aim of this study is to assess a pheromone complex-impregnated collar in the control of feline problem behaviors, and to assess the ease of use and tolerance of the collar compared with a regular collar. Six hundred and twenty-four cats from 459 households with one or more of four problem behaviors (problem urination, scratching, fear, or inter-cat conflict) were recruited to a 28-day study. Households were randomly assigned so that each cat received either a pheromone-impregnated polymer collar (containing 13% FELIWAY® Optimum) or a control regular silicone collar. Caregivers completed online questionnaires at recruitment and on days 7, 14, and 28 documenting the frequency and intensity of the problem behavior in the previous 7 days, and documenting any loss, problems and tolerance of the collar (pheromone-impregnated or control). Complete data was available for 491 cats for assessment of efficacy. Compared with the control collar, the pheromone collar produced significantly better improvement in problem urination (P = 0.0172), scratching (P = 0.0013), and inter-cat conflict (P = 0.0029). There was also a greater, but non-significant improvement in problem fear scores (P = 0.063). Collars had been removed definitively or lost from 12.1% of cats, for various reasons, by the end of the study, and potential adverse reactions were reported in 27.2% of cats, but again, with no difference in the overall frequency reported between the two collar groups. In a controlled study, a FELIWAY® Optimum-impregnated collar was shown to be effective in helping to manage a range of problem feline behaviors. The use of the pheromone collar was not associated with a higher level of adverse reaction reporting, but caregiver removal or loss of collars may present an obstacle for effective therapy through this means.